EVALUATING JOB CHARACTERISTICS, PSYCHOLOGICAL STATES, AND OUTCOMES OF HOSPITAL NURSES USING JOB DIAGNOSTIC SURVEY: DESCRIPTIVE QUANTITATIVE - Nabila, Zahratul; Riamanda, Irin (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2025)
Background: Nurses often face thevarious problems such as high workload, medical errors, lack of autonomy, and limited psychological support, which affect motivation, satisfaction, and quality of care. Purpose: To diagnose nurses' performance using the Job Diagnostic Survey (JDS) developed by Hackman and Oldham (1975). Methods: Used a quantitative method with a descriptive design and involved 160 nurses at X Hospital who had worked for at least the last six months. The research instrument has gone through a try-out test on 62 respondents with reliability results ranging from 0.772-0.910 and item differentiability index between 0.333-0.857. Results: Most of the dimensions of work, psychological conditions, and affective responses of nurses were below the JDS category standards. The mean values for Skill Variety (4.62), Task Identity (4.82), Task Significance (4.62), Autonomy (4.54), and Feedback (4.42). Psychological dimensions such as Experienced Meaningfulness (4.42), Experienced Responsibility (5.10), and Knowledge of Results (4.56), and affective dimensions such as General Satisfaction (4.56) and Internal Work Motivation (4.96) were below the standard. Only Specific Satisfaction (5.34) was above the category’s standard. Conclusion: Nurses' job satisfaction and motivation are low due to lack of task variety, autonomy, and feedback. Abstrak Latar Belakang: Perawat yang sering menghadapi berbagai masalah seperti beban kerja tinggi, kesalahan medis, kurangnya otonomi, dan dukungan psikologis terbatas, yang memengaruhi motivasi, kepuasan, dan kualitas pelayanan. Tujuan: Untuk mendiagnosa kinerja perawat menggunakan Job Diagnostic Survey (JDS) yang dikembangkan oleh Hackman dan Oldham (1975). Metode: Menggunakan metode kuantitatif dengan jenis deskriptif dan melibatkan 160 perawat di Rumah Sakit X yang telah bekerja minimal enam bulan terakhir. Instrumen penelitian telah melalui uji try out pada 62 responden dengan hasil reliabilitas berkisar antara 0,772–0,910 dan indeks daya pembeda item antara 0,333–0,857. Hasil: Sebagian besar dimensi pekerjaan, kondisi psikologis, dan respons afektif perawat berada di bawah standar kategori JDS. Nilai mean untuk Skill Variety (4,62), Task Identity (4,82), Task Significance (4,62), Autonomy (4,54), dan Feedback (4,42). Dimensi psikologis seperti Experienced Meaningfulness (4,42), Experienced Responsibility (5,10), dan Knowledge of Results (4,56), dan dimensi afektif seperti General Satisfaction (4,56) dan Internal Work Motivation (4,96) berada di bawah standar. Hanya Specific Satisfaction (5,34) berada di atas standar kategori. Kesimpulan: Kepuasan kerja dan motivasi perawat rendah karena kurangnya variasi tugas, otonomi, dan umpan balik.